SEASONAL VARIATION AND ALGAL DIVERSITY IN THE HIGHLY ALKALINE SOLID WASTES FROM A PAPER MILL IN SOUTHERN ASSAM (INDIA) - AMALINA PAUL,; JAYASHREE ROUT, (International Journal of Pharma and Bio Sciences, 2016)
Algae represent cosmopolitan prokaryotes, occurring in almost every aquatic and terrestrial environment including soil, in fresh water, in salt water and as well as in several surface types. The capability of cyanobacteria to fix molecular nitrogen together with their desiccation tolerance, renders them to be the most successful colonizers in low-fertility, high-pH sites. Current research has addressed to recover, stabilize and utilize degraded soils through the use of various algae. Besides chemical and physical methods, such algae based biological remediation processes are considered eco-friendly and cost effective. In this study, we investigated the soil algae inhabiting lime sludge waste generated by a Paper Mill, in Hailakandi district, Assam in India. Studies conducted on the seasonal distribution of algal communities revealed the occurrence of a total of 18 algal species belonging to 14 genera with predominant presence of Cyanobacteria followed by Chlorophyceae and Bacillariophyceae. Distribution of the algal genera was varied in different seasons, i.e. highest in monsoon and post-monsoon period and least in pre-monsoon period. Predominant blue - green alga was Oscillatoria, while Cosmarium was the most dominant green alga recorded. Different diversity indices were ascertained and correlation study made. Highest diversity was noted during the post-monsoon period.